Distinguishing the papilla of Vater during biliary cannulation using texture and color enhancement imaging: A pilot study. Issue 1 (15th May 2022) - Miyaguchi, Kazuya; Mizuide, Masafumi; Tanisaka, Yuki; Fujita, Akashi; Jinushi, Ryuhei; Hiromune, Katsuda; Ogawa, Tomoya; Saito, Yoichi; Tashima, Tomoaki; Mashimo, Yumi; Imaeda, Hiroyuki; Ryozawa, Shomei
Abstract: Objectives: Understanding the exact morphology of the bile duct opening is important for determining the success of bile duct cannulation. Texture and color enhancement imaging (TXI) has been reported to enhance slight changes in color tone and structure that are difficult to see with white light imaging. This study investigated whether TXI mode1 could improve papillary recognition by trainees inexperienced in endoscopic retrograde cholangiopancreatography. Methods: We included 31 patients with naive papilla of Vater at a single institution in the study. Trainee endoscopists (n = 4) evaluated and identified the papilla according to the Inomata classification using white light imaging and TXI. The degree of agreement with the evaluation of supervising physicians ( n = 4) was examined using the McNemar test. Results: In the trainee group, the kappa coefficient agreements were κ = 0.346 and κ = 0.754 for white light imaging and TXI, respectively. When further evaluated, the separate and septal types of papilla groups showed an increased concordance rate in one of the four trainees (76.67%–96.67%, p = 0.031, respectively). Moreover, comparison for two‐group evaluation showed an increased kappa coefficient in two of four trainees (0.34–0.92, p = 0.010, 0.45–0.92, p = 0.024). Conclusions: Observation of the duodenal papilla using TXI improved papillary differentiation and suggested the potential of TXI as a clinical tool. Further study of this method is necessary; it is expected to help reduce cannulation time and the incidence of pancreatitis.